Implementation of the Merdeka Curriculum and its Impact on Effective Learning Achievement in Elementary School - Lara Prahastina; Mintasih Indriayu; Matsuri Matsuri (Universitas Sebelas Maret, 2024)
The study on the Implementation of the Merdeka Curriculum at elementary school, reveals a positive overall readiness and commitment among teachers to adapt to changes in the learning approach. Through interview analysis, it is evident that teachers comprehend the Merdeka Belajar concept and are prepared to embrace the new curriculum, emphasizing creativity and innovation. Significant obstacles arise from differences with the previous curriculum, notably in project-based learning assessments, necessitating deeper understanding and additional training. The assessment aspect analysis indicates effective implementation of formative and authentic assessments by teachers. However, challenges linked to the lack of understanding among teachers and parents about the Merdeka Curriculum, particularly Merdeka Belajar, may impact curriculum goal achievement. Consequently, concerted efforts are required to improve parental understanding and support, along with additional training for teachers regarding assessment within the Merdeka Curriculum context. The curriculum encourages teachers to design more engaging and interactive learning experiences, granting students the freedom to choose subjects and unlocking opportunities to explore talents and potentials in various fields.